A narrative review and expert panel recommendations on dyslipidaemia management after acute coronary syndrome in countries outside western Europe and North America (2020)
Patients who have experienced an acute coronary syndrome (ACS) are at very high risk of recurrent atherosclerotic cardiovascular disease (CVD) events. Dyslipidaemia, a major risk factor for CVD, is poorly controlled post ACS in countries outside Western Europe and North America, despite the availability of effective lipid-modifying therapies (LMTs) and guidelines governing their use. Recent guideline updates recommend that low-density lipoprotein cholesterol (LDL-C), the primary target for dyslipidaemia therapy, be reduced by C 50% and to \1.4 mmol/L (55 mg/dL) in patients at very high risk of CVD, including those with ACS. The high prevalence of CVD risk factors in some regions outside Western Europe and North America confers a higher risk of CVD on patients in these countries. ACS onset is often earlier in these patients, and they may be more challenging to treat. Other barriers to effective dyslipidaemia control include low awareness of the value of intensive lipid lowering in patients with ACS, physician non-adherence to guideline recommendations, and lack of efficacy of currently used LMTs. Lack of appropriate pathways to guide follow-up of patients with ACS post discharge and poor access to intensive medications are important factors limiting dyslipidaemia therapy in many countries. Opportunities exist to improve attainment of LDL-C targets by the use of country-specific treatment algorithms to promote adherence to guideline recommendations, medical education and greater prioritisation by healthcare systems of dyslipidaemia management in very high risk patients.